STUDIES ON PLOTINUS AND AL-KINDI - Adamson, Peter, 1972- author. ([S.l.])
1 online resource
Keywords: This book collects 15 papers on the greatest philosopher of late antiquity and founder of Neoplatonism, Plotinus (d.270), and the founding figure of philosophy in the Islamic world: al-Kind (d. ca. 873). A number of the contributions focus on the text that joins the two: the so-called Theology of Aristotle, in fact an Arabic version of Plotinus' Enneads produced in al- Kind's translation circle. Across several papers, Adamson argues that this translation is best understood as a reinterpretation of Plotinus designed to appeal to contemporary readers in the culture of the 'Abbsid era. Two contributions also analyze the notes on the Theology written by the great Avicenna. Other papers look at aspects of al-Kind's own thought, exploring his ideas concerning metaphysics, free will astrology, and optics. The traditions of Plotinus and al-Kind are also treated, with papers on Plotinus' student Porphyry and his Arabic reception, and on followers of al-Kind. Adamson argues that we can identify what he calls a 'Kindian tradition' in the 9th-10th centuries. He discusses the philosophical presuppositions of this movement, and the use of al-Kind's ideas made by one particular representative of the Kindian tradition, the Persian thinker Miskawayh.